High-Yield Production of SiV-Doped Nanodiamonds for Spectroscopy and Sensing Applications - Kromka, Alexander; Varga, Marián; Aubrechtová Dragounová, Kateřina; Babčenko, Oleg; Pfeifer, Rene; Flatae, Assegid M; Sledz, Florian; Akther, Farzana; Agio, Mario; Potocký, Štěpán; Stehlík, Štěpán (ACS applied nano materials, 2024)
Nanodiamonds (NDs) containing optically active centers have gained significant relevance as the material of choice for biological, optoelectronic, and quantum applications. However, current production methods lag behind their real needs. This study introduces two CVD-based approaches for fabricating NDs with optically active silicon-vacancy (SiV) color centers: bottom-up (BU) and top-down (TD) methods. The BU approach generates nanoporous diamond films with a core-shell structure, while the TD method employs molten-salt thermal etching to create uniform porous structures from nanocrystalline diamond films. Comprehensive characterization using advanced techniques revealed distinct morphologies and optical properties for each approach. The BU method yielded higher-quality diamond phases with top-surface incorporation of SiV centers, while the TD method demonstrated efficient nondiamond phase removal. Ultrasonic disintegration of both porous films produced NDs ranging from 40 to 500 nm, with unique morphologies characteristic of each approach. Photoluminescence measurements confirmed SiV centers (738 nm) in all NDs, exhibiting sensitivity to surface terminations, particularly in BU samples. Temperature-resolved spectroscopy shows the potential of the fabricated NDs for nano thermometry over a wide range of temperatures up to 100 °C. The zero-phonon line shows 0.022 ± 0.003 nm/K sensitivity, while the line width exhibits 0.068 ± 0.004 nm/K broadening. The presented BU and TD methods offer significant advantages over existing techniques, including streamlined production processes, high-yield ND synthesis with tailored properties, and the potential for scalable, cost-effective manufacturing.